2004
DOI: 10.1002/j.1551-8833.2004.tb10706.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infectious Cryptosporidium in Filtered Drinking Water

Abstract: Monitoring of 82 surface water treatment plants revealed that 1.4% of 1,690 100‐L finished water samples tested positive for infectious Cryptosporidium using the cell culture‐polymerase chain reaction). Infectious oocysts were detected in finished water samples from 22 water treatment plants (26.8%). Genotype analysis identified 23 isolates as Cryptosporidium parvum and one isolate as Cryptosporidium hominis. All isolates subgenotyped were shown to be genetically distinct environmental isolates. Analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 22 publications
(32 reference statements)
0
41
0
5
Order By: Relevance
“…The disease cryptosporidiosis is usually a self-limiting diarrhea in healthy adults but may be life threatening for persons with weakened immune systems. Cryptosporidium oocysts are ubiquitous in environmental waters, are resistant to chlorination, and have been found in treated drinking water (1,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The disease cryptosporidiosis is usually a self-limiting diarrhea in healthy adults but may be life threatening for persons with weakened immune systems. Cryptosporidium oocysts are ubiquitous in environmental waters, are resistant to chlorination, and have been found in treated drinking water (1,18).…”
mentioning
confidence: 99%
“…The use of cell culture to study the intracellular development of Cryptosporidium was described over 2 decades ago (6). In addition to the study of Cryptosporidium biology, cell culture methods have been used to study Cryptosporidium inactivation by disinfectants (4,13,23,26,28), efficacy of chemotherapeutic agents (3,5,34,37), and detection of infectious oocysts in water samples (1,7,10,17). The developmental stages of the parasite in cell culture are detected using a variety of techniques, including immunofluorescent assay microscopy (27), flow cytometry (31), reverse transcription-PCR (22), and quantitative PCR (5,8,11,15).…”
mentioning
confidence: 99%
“…Therefore, incubation periods may have an effect on the ability to detect infection, particularly with very low numbers of infectious oocysts. In our previous studies using conventional CC-PCR to assay environmental samples, an incubation period of 72 h was used, which may have aided the detection of low numbers of naturally occurring C. parvum oocysts (1,7,19). Therefore, on the basis of our successful CC-PCR analysis of environmental water samples and the CC-QSD data presented here, we recommend a 72-h incubation period for the CC-QSD method.…”
Section: Discussionmentioning
confidence: 96%
“…Turbidity and particle number removal was lower than oocysts removal. Aboytes et al (1), however, investigating 82 conventional (rapid) filters, found no differences in water quality (turbidity and microbial indicators) between sites with and without infectious oocysts in filtered waters.…”
Section: Introductionmentioning
confidence: 92%